Improving the Ability to Write Descriptive Texts through the Field Trip Method for Grade VII Students of MTs Muhammadiyah Bengkulu - Zona Amalia; Reni Kusmiarti; Eli Rustinar (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Writing skills are one of the important aspects of learning Indonesian, especially in writing descriptive texts. This research aims to improve the ability to write descriptive texts of grade VII students of MTs Muhammadiyah Bengkulu through the application of the Field Trip to Cinema method as an audiovisual experience. This study uses the Kemmis & McTaggart Class Action Research (PTK) model approach which includes the stages of planning, action, observation, and reflection. The research subjects consisted of 25 students, with data collected through observation of teacher and student activities and descriptive text writing skills tests. The results of the study showed a significant improvement in students' writing skills. In the first cycle, the completeness of classical learning reached 64%, not meeting the Minimum Completeness Criteria (KKM) 75, with most students in the adequate and inadequate categories. After improvement and re-application in cycle II, learning completeness increased to 100%, with most students obtaining good and excellent category scores. Teacher activity and student enthusiasm also showed an increase in cycle II. These findings confirm that the Field Trip method is not only effective in improving writing skills, but also provides a contextual, creative, and interesting learning experience, so that it can be used as an innovative alternative in learning to write descriptive texts at the junior high school/MTs level.